Assessment of genotoxicity and cholinesterase activity among women workers occupationally exposed to pesticides in tea garden - V, Dhananjayan; B, Ravichandran; K, Panjakumar; K, Kalaiselvi; Rajasekar, Kausic; A, Mala; G, Avinash; K, Shridhar; A, Manju; Wilson, Rajesh (Mutation research, 2019)
•Lower cholinesterase activity and DNA damage was associated with occupational exposure to pesticide.•No significant impact of confounding factors on cholinesterase activity and comet assay parameters.•Multiple intervention techniques such usage of PPE, awareness programmes including education and training are required for the workers.•This study demonstrates the need of further longitudinal study for better understating of the exposure and effects. To assess the effects of exposure to pesticides in tea garden women workers, the present study evaluated the activities of erythrocyte acetylcholinesterase (AChE) and plasma butyrylcholinesterase (BChE) as biomarkers of pesticide exposure and DNA damage by comet assay as a biomarker of genotoxicity in peripheral blood lymphocytes. We examined 143 women subjects including 77 women workers exposed to pesticide in tea garden (exposed) and 66 women subject with no history of occupational exposure to pesticides (non-exposed). The two groups had similar mean ages, BMI and personal habits. The results revealed that exposed group had lower activity of AChE (2.86 ± 0.75 vs. 3.93 ± 0.87 U/ml) BChE (2.02 ± 0.74 vs. 2.60 ± 0.74 U/ml, p < 0.001) than those of non-exposed group. The mean comet parameters such as tail length (TL), % DNA in tail, tail moment (TM) and olive tail moment (OTM) used to measure DNA damage were significantly elevated in exposed workers compared to non-exposed (p < 0.001). There was no variation observed in Cholinesterase (ChEs) activity and Comet assay parameter based on age, personal habits, years of exposure and use of personal protective equipments (PPEs) except BChE activity. The multiple regression analysis showed no association of confounding factors on end points measured except slight negative association of BMI with tail length. Therefore this study suggests that the workers in tea garden might have exposed to pesticide through their occupation on a regular interval. Although this study could able to associate it with their occupational exposure, the role of other DNA damaging factors cannot be ruled out. Our study finding indicate the necessity of periodic monitoring of these biomarkers along with imparting education and training to minimise the risk.